Guidance/Training Course in Facing the Psychological Pressures and Improving the Speed and Performance of Football Referees for Iraqi Premier League - Al Qaysi, Ali; Baaziz, Mohamed; Boukari, Samia; Attia, Ahmed; Turki, Olfa; Chortane, Sabri Gaied; Khalifa, Riad (Advances in Social Sciences Research Journal, 2024)
The study aimed to identify the effect of the guidance and Program in Facing the Psychological Pressures and Improving the Speed, its Endurance and Performance of Football Referees for Iraqi Premier League. The equal-group experimental method has been used. The groups are two experimental groups and a control group with pre- and post-measurements. The study sample consisted of (30) referees. They were selected randomly and by lottery. They were distributed into two experimental groups (the first experimental group takes the training curriculum, the second experimental group takes the training curriculum and the guidance program), and the third group is the control. Each group consists of ten referees. Having done that, the normal distribution was conducted by using the skewness and variation coefficients. while homogeneity was used by Levene’s test for homogeneity and the (F) test for equality. The researcher conducted an exploratory experiment, which focused on identifying the field difficulties that the researcher may face during the actual conduct of the guidance and training program. The SPSS statistical software has been used. The results of the study showed the improvement of the second experimental group, followed by the first experimental group, and then the control group. Accordingly, the researcher concluded that the guidance and training program improved the referee’s performance.